Sequence and functional similarity between a yeast ribosomal protein and the Escherichia coli S5 ram protein. - All-Robyn, J A (1990)
The accurate and efficient translation of proteins is of fundamental importance to both bacteria and higher organisms. Most of our knowledge about the control of translational fidelity comes from studies of Escherichia coli. In particular, ram (ribosomal ambiguity) mutations in structural genes of E. coli ribosomal proteins S4 and S5 have been shown to increase translational error frequencies. We describe the first sequence of a ribosomal protein gene that affects translational ambiguity in a eucaryote. We show that the yeast omnipotent suppressor SUP44 encodes the yeast ribosomal protein S4. The gene exists as a single copy without an intron. The SUP44 protein is 26% identical (54% similar) to the well-characterized E. coli S5 ram protein. SUP44 is also 59% identical (78% similar) to mouse protein LLrep3, whose function was previously unknown (D.L. Heller, K.M. Gianda, and L. Leinwand, Mol. Cell. Biol. 8:2797-2803, 1988). The SUP44 suppressor mutation occurs near a region of the protein that corresponds to the known positions of alterations in E. coli S5 ram mutations. This is the first ribosomal protein whose function and sequence have been shown to be conserved between procaryotes and eucaryotes.